Investigating cost-effective policy incentives for renewable energy in Japan: A recursive cge approach for an optimal energy mix - Michael C. Huang; Chul Ju Kim (Asian Development Bank Institute (ADBI), 2019)
The Great East Japan Earthquake (GEJE) and Fukushima nuclear disaster that occurred in 2011 gave a sharp reminder to Japan's energy security to reconsider the reduction of nuclear power dependence with a better energy mix. We use a recursive CGE model based on Japan's renewable energy input-output model to analyze the energy composite of power generation and consumption to investigate cost-effective policy incentives to achieve an optimal energy mix with the goal of reducing the nuclear power dependence to less than 5% within 20 years. Moreover, we create scenarios of (1) nuclear power decommission, (2) renewable energy promotion, and (3) virtual power plant (VPP) implementation with public R&D expenditure and power infrastructure investment. The simulation results show that renewable energy could gradually replace nuclear power with capital-use subsidies. Most important of all, the implementation of VPPs could reduce both the fiscal costs and social costs of promoting renewable energy while facilitating power generation.
Keywords: C6; Q4; 330; recursive CGE model; renewable energy; Japan; optimal energy mix